Advancements in Low-Temperature Lithium Metal Batteries: A Comprehensive Review - Li, Aoxuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Lithium metal batteries (LMB) represent a major advance in energy storage technology, offering a huge high energy density, and have the potential to be used in important fields such as electric vehicles and aerospace. However, their practical application at low temperatures still faces major challenges. This paper reviews recent advances in overcoming these obstacles, including the development of ether-based and fluorated electrolytes to reduce dendrite formation, improve SEI stability, and the use of 3D collectors and protective coatings to create more stable interfaces. By combining these methods, we conclude from a large number of studies that the problem of LMB at low temperatures is not the result of a single aspect, but the result of multiple factors. SEI instability leads to uneven lithium deposition and electrolyte decomposition in LMB. At the same time, the ionic conductivity of the electrolyte decreases at low temperature, slowing down the transmission rate of lithium ions, resulting in an increase in overpotential and promoting the uneven deposition of lithium. Therefore, this paper proposed a feasible path for the future development of LMB, that is, strengthening the three-dimensional lipophilic skeleton while improving the electrolyte solution, and constructing the three-dimensional lipophilic skeleton of SEI to solve the problems of lithium dendrite growth of LMB at low temperature and SEI instability.